2013
DOI: 10.1002/ana.23943
|View full text |Cite
|
Sign up to set email alerts
|

TORC1‐dependent epilepsy caused by acute biallelic Tsc1 deletion in adult mice

Abstract: Commentary The dentate gyrus (DG) is thought to serve as a gate regulating the spread of excitatory input from the entorhinal cortex into the hippocampus (1). Breakdown of this gating function in the DG has been hypothesized to promote development of epileptogenesis in temporal lobe epilepsy (1, 2). A variety of pathological changes in DG granule cells in animal models and patients with temporal lobe epilepsy may contribute to disrupted DG function, including somatic hypertrophy, formation of basilar dendrites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 39 publications
9
71
0
Order By: Relevance
“…However, it is also likely that mTOR regulates neuronal excitability in already established neural circuits. Consistent with this model, Tsc1 inactivation in adult mice is rapidly followed by mTOR-dependent seizures(Abs et al, 2013). …”
Section: Neuropathology Of Mtormentioning
confidence: 63%
“…However, it is also likely that mTOR regulates neuronal excitability in already established neural circuits. Consistent with this model, Tsc1 inactivation in adult mice is rapidly followed by mTOR-dependent seizures(Abs et al, 2013). …”
Section: Neuropathology Of Mtormentioning
confidence: 63%
“…On the molecular level, homozygous Tsc1 deletion was associated with a significant reduction of the Tsc1 gene product (hamartin) as well as disinhibition of mTOR activity. Albeit this manipulation was lethal within weeks, the results demonstrated that acute loss of Tsc1 in the adult brain was sufficient to induce epileptogenesis, since structural abnormalities were absent in these mice and rapamycin treatment reduced seizure rates and increased survival (Abs et al, 2013). Moreover, these studies suggest that altered mTOR signalling may be a key mechanism of epileptogenesis in TSC.…”
Section: Tsc1 Mutantsmentioning
confidence: 81%
“…But seizures did occur when Tsc1 was acutely inactivated in all (i.e. neuronal and non-neuronal) adult cells (Abs et al, 2013). On the molecular level, homozygous Tsc1 deletion was associated with a significant reduction of the Tsc1 gene product (hamartin) as well as disinhibition of mTOR activity.…”
Section: Tsc1 Mutantsmentioning
confidence: 99%
“…Of course, a critical unanswered question remains about the extent to which seizures in these disorders reflect network disruption owing to the cortical malformation versus the effects of hyperactivated mTOR signalling. In one compelling study, inducible knockout of Tsc1 in adult rats led to rapid onset of severe seizures without having effects on brain structure, suggesting that mTOR activation is particularly relevant for seizure onset 54 .…”
Section: Megalencephaly-capillary Malformation Syndromementioning
confidence: 99%